Characterization of lasing-oscillation direction in optical gain-clamped erbium-doped fiber amplifiers - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Subramaniam, T.; Ahmad, Harith (Elsevier, 2007)
In this paper, the effect of ring-laser propagating direction in gain-clamped erbium-doped fiber amplifiers is investigated. The optical amplifier architecture under study is based on ring-laser cavity. The strongest gain-clamping effect is obtained for bi-traveling ring-laser in the optical amplifier. On the other hand, the low-noise figure operation can be achieved by allowing the ring-laser to co-travel with the signal propagation. (c) 2006 Elsevier Ltd. All rights reserved.